Tajweed Rules Haptic Application with Sound for Visually Impaired People - Azman, Atiqah Shahirah (IRC, 2015)
Every Muslim in this world needs to read Quran as one of religion activities in Islam. Quran can be read in a book and even in digitalized form of Quran such as in mobile phones and also electronic type of Quran. However, blind people are unable to read Quran in book form and digitalized form. Therefore, this project aims to address the problems faced by blind people and partially impaired people to learn on how to recite Quran with right Tajweed which synchronizes audio and haptic. Interview session with blind people and partially impaired people will be done to determine what are the limitations and problems faced by them during reciting Quran. Respondents from Malaysian Association for the Blind (MAB) will be the main focus group for this project. Hence, this research study will discover ways to help blind people and partially impaired people to read Quran with right Tajweed and right pronunciation. This project is hoped to successfully help blind people and partially impaired people to teach and learn on how to recite Quran properly with the help of Braille Line 20 haptic and audio application.